Ethics briefings - Tizzard, J. (Journal of medical ethics, 2008)
In January 2008, the Government-commissioned Organ Donation Taskforce published its report on organ donation in the UK. Established in December 2006, the Taskforce was given the brief of identifying barriers to donation and transplantation and suggesting solutions aimed at closing the widening gap between the number of donated organs and the number of those waiting for a transplant.Implementation of the Taskforce’s 14 recommendations, which were accepted in full by the Government, would constitute a radical reorganisation of the organ donation and transplant system in the UK. With £11 million committed by the Government, work will begin to establish an Organ Donation Organisation which will centrally employ transplant coordinators.Although NHS Trusts will no longer employ the transplant coordinators, they will have other responsibilities, most notably to set up the post of a clinical donor champion, who will seek to maximise donation locally, oversee training and report donation activity to a donation committee in each Trust. The aim of these moves is to make donation a normal occurrence within the NHS.This focus on local implementation will be backed up by a national framework of monitoring, coordination and guidance. According to the report, there are a number of legal and ethical issues surrounding donation that need to be resolved. When people die in intensive care, treatment can be withdrawn in a controlled way. However, when someone dies on a hospital ward and either they or their relatives have consented to donation, steps need to be taken to preserve the organs for transplantation. The Taskforce recommended that such issues are urgently addressed and that an independent UK-wide Donation Ethics Group should be established.Finally, the Taskforce report recommended better public recognition and promotion of organ donation. Black and minority ethnic communities in particular need to be approached in order to increase …